Analisis Kesalahan Siswa Kelas VII Dalam MemecahkanSoal Matematika Model Pisa Konten Quantity - Khoirun Nisa, Maryam; , Sri Rejeki M.Pd, M.Sc (2017)
Maryam Khoirun Nisa/A410130051. ERROR ANALYSIS SEVENTH GRADE MATHEMATICAL PROBLEMS PISA CONTENT MODELS QUANTITY. Essay, Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta, March, 2017. This study is aimed to describe, calculate the percentage and to find out the factors that cause the student's error in solving mathematics exercise based on PISA in quantity content. The type of this study is qualitative descriptive study. The subjects of research ere VII G grade of SMP Negeri 1 Kartasura, which amounted to 32 students. The technique of collecting data is using observation method, test, interview, and documentation. Triangulation was done to validate the data by comparing the data of the test method, interview and documentation. The technique of analyzing data is used by phasing the data reduction, data presentation, verivication, and conclusion. The analytical framework is developed by Polya problem solving with the Newman's error cetegories. The results of research are obtained 4 types of error and the percentage of each error includes the error of comprehension errors 10,97%, transformation errors 4,52%, processing skill errors 40,65%, and ecconding 63,87%. The results showed that processing errors and econding is the more dominant errors than the other error. Generally, the factors that cause the error are including the confusion of the students, the ability of reasoning, and the low of student's creativity to solve the obvious context problem, to manipulate into numeral form, and the students to use the process of the problem solving correctly according to Polya steps. Keywords: error, math problems, PISA, quantity